Human isotype‐dependent inhibitory antibody responses against Mycobacterium tuberculosis - Natalie Zimmermann; Verena Thormann; Bo Hu; Anne‐Britta Köhler; Aki Imai‐Matsushima; Camille Locht; Eusondia Arnett; Larry S Schlesinger; Thomas Zoller; Mariana Schürmann; Stefan HE Kaufmann; Hedda Wardemann (EMBO Molecular Medicine)
Abstract Accumulating evidence from experimental animal models suggests that antibodies play a protective role against tuberculosis (TB). However, little is known about the antibodies generated upon Mycobacterium tuberculosis (MTB) exposure in humans. Here, we performed a molecular and functional characterization of the human B‐cell response to MTB by generating recombinant monoclonal antibodies from single isolated B cells of untreated adult patients with acute pulmonary TB and from MTB‐exposed healthcare workers. The data suggest that the acute plasmablast response to MTB originates from reactivated memory B cells and indicates a mucosal origin. Through functional analyses, we identified MTB inhibitory antibodies against mycobacterial antigens including virulence factors that play important roles in host cell infection. The inhibitory activity of anti‐MTB antibodies was directly linked to their isotype. Monoclonal as well as purified serum IgA antibodies showed MTB blocking activity independently of Fc alpha receptor expression, whereas IgG antibodies promoted the host cell infection. Together, the data provide molecular insights into the human antibody response to MTB and may thereby facilitate the design of protective vaccination strategies.